The Impact of Political Variables on the Deterioration of Landmarks in Central and Northern Iraq with a Contemporary Geographical Perspective - Salam, Naseef .J. Aswad (Journal of Tikrit University for Humanities, 2020)
Iraq enjoys strategic importance distinct politically and economically as it contains the advantages of location, despite the events and political changes that plagued and geopolitical decline at the regional level, as witnessed by the terrorist operations led to the deterioration of many sectors, including tourism, which is an important economic power for the strength of the state. Iraq has features of civilization with indications that refer to the oldest historical legacy and geographical distribution extending from north to south, in addition to the available resources of hydrocarbons available and gave it a source of strength for political unity. However, in spite of these elements, the hands of international terrorism reached in mid-2014 to those landmarks with a cultural, strategic and economic dimension over the past centuries to turn them into empty ruins due to the sharpness of ideological extremism and logistic guidance in the destruction of those evidences that embody the heart of the civilization of Mesopotamia. Rhetoric rituals paint the road map to penetrate the tearing apart of the social fabric in Iraq, embodied in several nationalities and sects that derive their existence and strengthen their ties from those landmarks, which were destroyed by those groups in the spirit of ideological thought, which feeds on a global ideology with a geo-strategic scheme which aimed to cause the decay and disappearance of these spiritual places by the mattocks of darkness to change the geopolitics of the region.